Analisis Peran Pola Asuh Demokratis Orangtua Dalam Memotivasi Belajar Siswa Pada Pembelajaran Pai - Sholiha, Alfiatus; Rahmania, Savira; Khotimah, Khorriyatul (Universitas Batanghari Jambi, 2023)
This study aims to examine the role of parents' democratic parenting in motivating student learning in PAI learning. Democratic parenting style emphasizes giving intensive attention to children by respecting the child's freedom but also accompanied by supervision from parents. This research is a type of qualitative research, the method used is a literature study (library rearch) by reviewing books and various trusted sources such as reputable journals and scientific papers. To obtain in-depth data the researcher then reads, examines and analyzes from various sources that are relevant to what the researcher is studying. The results of this study indicate that parents' democratic parenting style can encourage children to become independent individuals and also have high learning motivation. This is because children with good care from parents receive intensive attention and space is opened for them to express opinions. Parents also accustom children to study discipline, independence, and obedience to worship to be able to provide a role for children, especially in learning motivation.